2013
DOI: 10.7150/jca.5832
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Biomarkers and the Potential Role of Cancer Stem Cells

Abstract: Over 50% of patients with colorectal cancer (CRC) will progress and/or develop metastases. Biomarkers capable of predicting progression, risk stratification and therapeutic benefit are needed. Cancer stem cells are thought to be responsible for tumor initiation, dissemination and treatment failure. Therefore, we hypothesized that CRC stem cell markers (CRCSC) can identify a group of patients whom are at increased risk for recurrence or progression of disease. If proven correct, these CRCSC biomarkers may heral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 80 publications
1
45
0
3
Order By: Relevance
“…However, the markers that are currently known remain controversial for colon CSCs. Currently, CSCs are defined by expression of CD133, EpCAM, CD44, CD166, and Lgr5 [8,34,35]. Here, we demonstrated that CD133 and EpCAM are makers for EMT change of colon CSCs.…”
Section: Discussionmentioning
confidence: 72%
“…However, the markers that are currently known remain controversial for colon CSCs. Currently, CSCs are defined by expression of CD133, EpCAM, CD44, CD166, and Lgr5 [8,34,35]. Here, we demonstrated that CD133 and EpCAM are makers for EMT change of colon CSCs.…”
Section: Discussionmentioning
confidence: 72%
“…FIR total knockout, FIR −/− , mouse is embryonic lethal before E9.5, suggesting that FIR is essential for embryogenesis. Proteins expressed during embryogenesis disappear during development but are re-expressed in cancers [27, 28], suggesting that FIR is crucial for carcinogenesis as well.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] Although previous reports have focused on the possible relationship between CD44v and ovarian cancer survival, there is no unified view in this issue. 25,30,42,43 In regard to these unanswered questions, we used Kaplan-Meier analysis to evaluate the capacity of CD44 variant 6 expression to predict outcome in patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 97%